Perception of dentists toward over-the-counter or nonprescription dental products: A questionnaire-based survey - Sanjeev Vaid; Deepak Sharma; Atul Singh; Shanta Negi; Aditi Malhotra; Ankit Mahajan (Wolters Kluwer Medknow Publications, 2024)
Introduction: The oral health-care market has been one of the leaders in research on the chemistry and biology of the mouth, fostering the development of various oral care products that have significantly enhanced the lives of millions of people around the globe. Considering the many choices of over-the-counter (OTC) products available in the marketplace, it is increasingly difficult to select the proper products. Therefore, it is crucial to comprehend the many characteristics of these OTC dental medications. Aim: The aim of this study was to assess the perception and preference of dentists toward OTC or nonprescription dental products using a questionnaire. Materials and Methods: A questionnaire-based cross-sectional survey was conducted to assess the perception among dental surgeons regarding OTC dental products. One hundred and two filled questionnaires were received from various dentists through Google Forms. Data were analyzed using descriptive statistics. Results: A total of 102 filled questionnaires were received and analyzed using descriptive statistics. 27.5% of dental surgeons recommended toothbrushes and mouthwash for daily oral hygiene maintenance. 85% recommended mouthwash based on clinical experience with 53% preferring it to maintain gingival health. 89.2% thought that companies misinform people about their products, which sometimes leads to problems such as dental abrasion, gum recession, and hypersensitivity, and 94.1% believed that more stringent regulation should be made to control unscientific publicity of these products. Conclusion: Most of the dental surgeons recommended the use of OTC dental products based on clinical experience and the specific indication for underlying disease. The preferred products included toothpaste, toothbrushes, mouthwash, interdental cleaning aids, and herbal products. The majority of dentists thought that the indiscriminate use of OTC dental products could lead to dental abrasion and gum problems, so strict regulation on the sale of such products should be done.